Parent–Adolescent Relationship Factors and Adolescent Outcomes Among High‐Risk Families. Issue 5 (December 2016) - Withers, Mathew C.; McWey, Lenore M.; Lucier‐Greer, Mallory
Abstract : Using a stress‐process and attachment theory framework, we identified salient aspects of the parent–adolescent relationship and tested the extent to which those aspects were longitudinally associated with depression, withdrawal, delinquency, and aggressive behavior outcomes among a sample of high‐risk adolescents ( N = 498). First, four dimensions of the parent–adolescent relationship were identified: emotional closeness, communication, autonomy, and conflict. Next, latent profile analyses were conducted, and four distinct parent–adolescent relationship profiles emerged: secure, avoidant, anxious, and detached. Adolescent outcomes were assessed 2 years later. Results indicated that (a) adolescents in the avoidant and anxious profiles demonstrated higher depression symptoms than did those in the secure profile, (b) higher levels of aggression were demonstrated in the avoidant profile, and (c) higher levels of delinquency were demonstrated in the detached profile. Implications for parent–adolescent relationships and family therapy interventions are provided.